Firm age and job creation in the US - Henry R. Hyatt (IZA World of Labor, 2022)
Entrepreneurship is essential for a healthy labor market. Recent evidence shows that young businesses (at most ten years old) have, on average, accounted for all of US employment growth over the past few decades. New businesses are especially important for youth employment. However, these businesses tend to borrow a lot, and the credit constraints they face limit their ability to create jobs. Historically, much of the discussion regarding the economic importance of entrepreneurship has focused on small businesses. Empirical evidence increasingly suggests that, among small businesses, those that are young create the most jobs.
Keywords: L26; D21; L2; L25; M13; 330; entrepreneurship; employment; start-up; firm age; firm size; firm growth